2013
DOI: 10.1007/s00253-012-4650-7
|View full text |Cite
|
Sign up to set email alerts
|

amoA-encoding archaea in wastewater treatment plants: a review

Abstract: Recent evidence from natural environments suggests that in addition to ammonia-oxidizing bacteria, ammonia-oxidizing archaea (AOA) affiliated with Thaumarcheota, a new phylum of the domain Archaea, also oxidize ammonia to nitrite and thus participate in the global nitrogen cycle. Besides natural environments, modern data indicate the presence of amoA-encoding archaea (AEA) in wastewater treatment plants (WWTPs). To further elucidate whether AEA in WWTPs are AOA and to clarify the role of AEA in WWTPs, this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 64 publications
5
69
0
Order By: Relevance
“…Irrespective of soil pollution, thaumarchaeal "group 1.1b (Nitrososphaera clusters)" is found to be widely distributed in these soils. The dominance of group 1.1b in a range of soils as well as wastewater treatment plants has been noticed in earlier studies (Gubry-Rangin et al 2011;Pester et al 2012;Limpiyakorn et al 2013). Thaumarchaeal "group 1.1b" is shown to participate in ammonia oxidation of strongly acidic soils as well as in heavy metal-contaminated thermal spring (Hatzenpichler et al 2008).…”
Section: Community Structure Of Aobsupporting
confidence: 54%
“…Irrespective of soil pollution, thaumarchaeal "group 1.1b (Nitrososphaera clusters)" is found to be widely distributed in these soils. The dominance of group 1.1b in a range of soils as well as wastewater treatment plants has been noticed in earlier studies (Gubry-Rangin et al 2011;Pester et al 2012;Limpiyakorn et al 2013). Thaumarchaeal "group 1.1b" is shown to participate in ammonia oxidation of strongly acidic soils as well as in heavy metal-contaminated thermal spring (Hatzenpichler et al 2008).…”
Section: Community Structure Of Aobsupporting
confidence: 54%
“…AOA is widespread even in engineered systems such as FPETPs and WWTPs and have a potential role in removing nitrogen from wastewater. Previous phylogenetic studies of AOAamoA gene from WWTPs suggested that although AOA groups 1.1a and 1.1b were both present in WWTPs, the majority belonged to the Thaumarcheota group 1.1b [8,9]. Environmental factors are likely to play a role in defining the ecological niches of AOA [6,[21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have shown the presence of archaeal amoA genes in WWTPs and nitrogen removal reactors [9,14] suggesting that like in natural habitats [19]. AOA is widespread even in engineered systems such as FPETPs and WWTPs and have a potential role in removing nitrogen from wastewater.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations